2022
DOI: 10.3389/fgene.2022.959109
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of prognostic and immunologic characteristics associated with coronavirus disease 2019 regulators in acute myeloid leukemia

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has so far damaged the health of millions and has made the treatment of cancer patients more complicated, and so did acute myeloid leukemia (AML). The current problem is the lack of understanding of their interactions and suggestions of evidence-based guidelines or historical experience for the treatment of such patients. Here, we first identified the COVID-19-related differentially expressed genes (C-DEGs) in AML patients by analyzing RNA-seq from public databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In a systematic review by Reyes-Long et al (2023), they have demonstrated that microRNA expression levels differ between COVID-19 positive and negative patients, and these differences may be associated with the upregulation or downregulation of specific microRNAs 55 . Additionally, in the study by Shi et al (2022), differences in microRNA expression among patients are observed 56 . The present study also found that the expression levels of microRNAs differed between COVID-19 positive and negative patients, and some microRNAs exhibited increased expression.…”
Section: Discussionmentioning
confidence: 97%
“…In a systematic review by Reyes-Long et al (2023), they have demonstrated that microRNA expression levels differ between COVID-19 positive and negative patients, and these differences may be associated with the upregulation or downregulation of specific microRNAs 55 . Additionally, in the study by Shi et al (2022), differences in microRNA expression among patients are observed 56 . The present study also found that the expression levels of microRNAs differed between COVID-19 positive and negative patients, and some microRNAs exhibited increased expression.…”
Section: Discussionmentioning
confidence: 97%